Nitrogen balance for potato crops in the southeast pampas region, Argentina - Giletto, Claudia Marcela; Echeverria, Hernan Eduardo (Springer, 2018)
The aim of this work was to build an N mass balance for the potato crop under irrigation conditions in the southeast pampas (Argentina) as a function of N rate and gravitational water. The experiment was developed in a Typic Argiudoll soils during five growing seasons using N treatments. Yield, N concentration, N accumulated and dry matter content in the tubers were different between years by effect of the N rates, the irrigation management and precipitations. Fertilizer N recovery in tubers decreased as the N rate and the volume of gravitational water increased. Soil residual N increased with the N rate and decreased with gravitational water. N loss increased with the N rate and the volume of gravitational water, so it is highly possible that nitrate leaching is the most important loss process. N loss means ranged from 12 to 57 % with the lowest and highest hydric excess (73 and 479 mm, respectively). N loss may become the largest N sink when there is excess of water. It is recommended to adapt N fertilization strategies with a proper irrigation management.